ln(x+2)=7-ln(x+2)

Simple and best practice solution for ln(x+2)=7-ln(x+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for ln(x+2)=7-ln(x+2) equation:


Simplifying
ln(x + 2) = 7 + -1ln(x + 2)

Reorder the terms:
ln(2 + x) = 7 + -1ln(x + 2)
(2 * ln + x * ln) = 7 + -1ln(x + 2)
(2ln + lnx) = 7 + -1ln(x + 2)

Reorder the terms:
2ln + lnx = 7 + -1ln(2 + x)
2ln + lnx = 7 + (2 * -1ln + x * -1ln)
2ln + lnx = 7 + (-2ln + -1lnx)

Solving
2ln + lnx = 7 + -2ln + -1lnx

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Add '2ln' to each side of the equation.
2ln + 2ln + lnx = 7 + -2ln + 2ln + -1lnx

Combine like terms: 2ln + 2ln = 4ln
4ln + lnx = 7 + -2ln + 2ln + -1lnx

Combine like terms: -2ln + 2ln = 0
4ln + lnx = 7 + 0 + -1lnx
4ln + lnx = 7 + -1lnx

Add 'lnx' to each side of the equation.
4ln + lnx + lnx = 7 + -1lnx + lnx

Combine like terms: lnx + lnx = 2lnx
4ln + 2lnx = 7 + -1lnx + lnx

Combine like terms: -1lnx + lnx = 0
4ln + 2lnx = 7 + 0
4ln + 2lnx = 7

Reorder the terms:
-7 + 4ln + 2lnx = 7 + -7

Combine like terms: 7 + -7 = 0
-7 + 4ln + 2lnx = 0

The solution to this equation could not be determined.

See similar equations:

| -81=6v-13v-18 | | -5x-19=0 | | x^3-7x+6=x^2+2x-3 | | 7x^2+6=-118 | | 2x+y=31xy | | 7x^2-24x-9=0 | | 6x+2y+6x= | | 4x(-6)=4x(-5) | | -4(-6v-u)-3(3u+5v)= | | g(-4)=-4x-4 | | -2a^2+22a+121=0 | | a^2+22a+121=0 | | 8x+5=10x+23-8x | | (-3)(12)= | | x-29=19 | | 18=6(w+6)-8w | | 8x+2=1x-19 | | 5v-41=-6(v-6) | | 2m+12=-31 | | -2+2x=4+12x | | Y=-4x+340 | | 2x^2-5x-21=p | | 3b-3(-23+2b)=48 | | 5(x-3)-x= | | Tanx-cotx=0 | | 22=-3+5u | | 2(7p+8)+6(2p+8)= | | 10-5x-10x+4= | | 4c+30=4c+20 | | c/6+2=-1 | | 2x+1=11x-28 | | 5(3-x)-2(6-5x)=33 |

Equations solver categories